Plasma-membrane hyperpolarization diminishes the cation efflux via Nha1 antiporter and Ena ATPase under potassium-limiting conditions - Zahrádka, Jaromír; Sychrová, Hana (FEMS yeast research, 2012)
Saccharomyces cerevisiae extrudes K(+) cations even when potassium is only present in scarce amounts in the environment. Lost potassium is taken up by the Trk1 and Trk2 uptake systems. If the Trk transporters are absent or nonfunctional, the efflux of potassium is significantly diminished. A series of experiments with strains lacking various combinations of potassium efflux and uptake systems revealed that all three potassium-exporting systems the Nha1 antiporter, Ena ATPase and Tok1 channel contribute to potassium homeostasis and are active upon potassium limitation in wild-type cells. In trk1Δ trk2Δ mutants, the potassium efflux via potassium exporters Nha1 and Ena1 is diminished and can be restored either by the expression of TRK1 or deletion of TOK1. In both cases, the relative hyperpolarization of trk1Δ trk2Δ cells is decreased. Thus, it is the plasma-membrane potential which serves as the common mechanism regulating the activity of K(+) exporting systems. There is a continuous uptake and efflux of potassium in yeast cells to regulate their membrane potential and thereby other physiological parameters, and the cells are able to quickly and efficiently compensate for a malfunction of potassium transport in one direction by diminishing the transport in the other direction.
Keywords: draslíkové kanály; draslík; Sodium-Potassium-Exchanging ATPase; kationty; membránové potenciály; Saccharomyces cerevisiae Proteins; Cell Membrane; Potassium; Cations; Saccharomyces cerevisiae; Cation Transport Proteins; Sodium-Hydrogen Exchangers; Na(+)-H(+) antiport; proteiny přenášející kationty; Potassium Channels; buněčná membrána; Saccharomyces cerevisiae - proteiny; sodíko-draslíková ATPasa; Membrane Potentials